Arguments for democracy - "Benn, Tony" (London, 1981)
This book has been written for those of us who want to see people of this country take control of our own destinies and use the power of democracy to resolve the many pressing problems we face in our daily lives, including unemployment, injustice and the threat of War . It identifies some of the obstacles which now prevent us from taking effective action and is intended as a practical guide rather than an academic study.
Keywords: Democracy